FORMULATIF POLICY REMEDIES INDEPENDENT DECISION OF PUBLIC PROSECUTOR FOR PERSPECTIVE IN THE CRIMINAL JUSTICE SYSTEM OF INDONESIA - I Gede Artha (Kumpulan Jurnal Mahasiswa Fakultas Hukum, 2013)
ABSTRACTThis dissertation is a research of acquital (vrijspraak)in some criminal cases that were made by the judge, and related with the law effort of appellate and cassation. Due process of law in criminal justice of Indonesia tends to be notgiving satisfaction for the justice seekers. The many amount of criminal casesthat get acquital (vrijspraak) such as the cases of corruption, narcotic, murder, and others got opinion and contra from broad society. The practitioners andtheoreticians of law and so does the justice seekers often spotlight the judgeâ€™sverdict which is judged as the engineering of justice, full of mafia andfraudulence. The Procedure of Criminal of Indonesia based on the Criminal Code stills seem to contain disharmony of law norms such as not to give the authority to general prosecutor to submit law effort of appellate and cassation upon the acquital (vrijspraak) as written in the Article 67 and Article 244 of Criminal Code, so it creates the disharmony or injustice in the existing law norms about the acquital (vrijspraak) arrangement, it seems that there is an empty norm, even there is a blur norm in the procedure of criminal with Criminal Code as the basis. This research has purpose to give solution upon disharmony that happen in the acquital (vrijspraak) and its law effort for the general prosecutor. Beside that, it also gives a scientifically input for the theoreticians and practitioners. In studying of this acquital (vrijspraak), it uses some approaches, such as the statute approach, the analytical and conceptual approach, the case approach, the comparative approach, and the philosophical approach. The source of the researched law materials related with the primary, secondary, and tertiary law material. The future perspective of acquital (vrijspraak) arrangement construction related to appellate is: â€œTo criminal case verdict given in the first stage court, the defendant or the general prosecutor is able and or has authority to submit the appellate request to the high court including for free verdictâ€. And the construction of article for acquital (vrijspraak) for cassation is: â€œTo the criminal case verdict given in the last stage by other court except the Supreme Court, the defendant or general prosecutor is able and or has authority to submit the request for cassation to the Supreme Court including the acquital (vrijspraak)â€.Key words: formulation policy, acquital, procecutor, criminal justice system.